Laurence Alfred Mound and his contributions to our knowledge of the Thysanoptera - Funderburk, Joe; Hoddle, Mark (Zootaxa, 2011)
Laurence Alfred Mound became interested in taxonomy after two postgraduate periods at the British Museum of Natural History (now the Natural History Museum) in London where he discovered biological diversity and the endless variety of living things. While working in Nigeria and the Sudan, and studying variation in whitefly populations, he gained an appreciation for the great differences within species in behavior and morphology under varying environmental conditions. He was appointed to the British Museum of Natural History in 1964 where he worked on the taxonomy of thrips, whiteflies, and aphids until he retired as Keeper of Entomology in 1992. He now lives in Canberra, Australia, serving as an Honorary Research Fellow, CSIRO Ecosystem Sciences at the Black Mountain Campus. Driving questions motivate him and provide insight into his thinking of the natural world: Why are there so many species of insects, yet so few species of thrips? Why so many at one place but so few at another? Do environmental and host plant factors drive the astonishing levels of morphological variation seen in single species? If so why? Why do so few thrips vector plant viruses, but why are those few so successful? Why are so many thrips associated with Acacia trees in Australia but so few on other plants? To address these questions and as part of his ongoing efforts to document the biodiversity of thrips, Laurence Mound has established 90 new Thysanoptera genera, and described 641 new species of thrips. These taxonomic designations are new hypotheses inviting scrutiny and study.  At the time this document was written Laurence’s research articles had been cited almost 1,300 times. Here we review Laurence Mound’s career to this point, and we discuss the quality and quantity of his remarkable accomplishments in taxonomy, as well as highlighting his distinctive personal characteristics.